Midnight in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2005)
Eve's name has a made a Christmas list, but it's not for being naughty or nice. It's for putting a serial killer behind bars. Now the escaped madman has her in his sights. With her husband Roarke at her side, Eve must stop the man from exacting his bloody vengeance-or die trying.